Kilmer's pet monster - Jones, Marcia (Marcia Thornton); Dadey, Debbie; Gurney, John (New York : Scholastic, 1998)
Kilmer brings Priscilla's pet monster to Bailey City.
"A little apple paperback."
3
3-6
Keywords: Monsters -- Fiction; Pets -- Fiction; Horror stories; Monsters -- Fiction; Pets -- Fiction; Horror fiction